Tingkat Kecukupan Energi, Protein Dan Status Ketahanan Pangan Rumah Tangga Berhubungan Dengan Status Gizi Anak Usia 6-8 Tahun - Rika Kusuma Nagari; Triska Susila Nindya (Amerta Nutrition, 2017)
Background: The nutritional status of elementary school children can be influence by many factors such as levels adequacy of energy and proteinand household food security status. Unbalanced levels adequacy of energy and protein possibility can cause nutritional problems in children. While the status of household food security has an impact on the household ability to access a good food. Objectives: aims of this study are to analyze the relationship between nutritional adequacy level and household food security status with nutritional status of children aged 6-8 years. Method: This study used cross sectional design with sample of 62 families with children aged 6-8 years enrolled in SDN 1 and 2 Sambirejo. Anthropometric measurement of height and weight is used to determine the nutritional status of children. The instruments used 2x24-hours food recall form (energy and protein adequacy level), and US-HFSSM (household food security status). While the statistical test used is spearman correlation test. Results: The results showed a correlation between levels of energy (p=0.000) and protein (p=0.000) adequacy and household food security status (p=0.010) with child nutritional status. Conclusion: Households with food insecurity had a higher proportion of nutritional problem than food secure family, so it is needed to children for having supplemental food, especially them who have nutritional problems and on food insecurity condition. It is intended to provide children with additional nutritious food to reduce the risk of nutritional problems.ABSTRAK Latar Belakang: Status gizi anak sekolah dasar dapat dipengaruhi oleh banyak faktor diantaranya tingkat kecukupan energi dan protein serta status ketahanan pangan rumah tangga. Ketidakseimbangan tingkat kecukupan energi dan protein, kemungkinan dapat menyebabkan masalah gizi pada anak. Status ketahanan pangan rumah tangga berdampak kepada kemampuan dalam mengakses pangan yang baik.Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan antara tingkat kecukupan energi dan protein serta status ketahanan pangan rumah tangga dengan status gizi anak usia 6-8 tahun.Metode: Penelitian ini menggunakan desain cross sectional dengan sampel sebanyak 62 keluarga yang memiliki anak usia 6-8 tahun yang terdaftar di SDN 1 dan 2 Sambirejo. Pengukuran antropometri tinggi badan dan berat badan digunakan untuk mengetahui status gizi anak. Selain itu, instrumen yang digunakan adalah  formulir 2x24-hours food recall (tingkat kecukupan energi dan protein), dan US-HFSSM (status ketahanan pangan rumah tangga). Statistik uji yang digunakan adalah uji korelasi spearman.Hasil: Hasil dari penelitian ini yaitu terdapat hubungan antara tingkat kecukupan energi (p=0,000) dan protein (p=0,000) serta status ketahanan pangan rumah tangga (p=0,010) dengan status gizi anak.Kesimpulan: Rumah tangga yang rawan pangan akan memiliki risiko mengalami masalah gizi yang lebih tinggi bila dibandingkan dengan rumah tangga yang tahan pangan, sehingga perlu adanya pemberian makanan tambahan kepada anak, terutama kepada anak yang memiliki masalah gizi dan berada pada kondisi rawan pangan. Hal tersebut dimaksudkan untuk memberikan anak tambahan makanan yang bergizi agar menurunkan risiko masalah gizi.